Protection against Fatal Sindbis Virus Encephalitis by Beclin, a Novel Bcl-2-Interacting Protein - Liang, Xiao Huan (American Society for Microbiology, 1998)
bcl-2, the prototypic cellular antiapoptotic gene, decreases Sindbis virus replication and Sindbis virus-induced apoptosis in mouse brains, resulting in protection against lethal encephalitis. To investigate potential mechanisms by which Bcl-2 protects against central nervous system Sindbis virus infection, we performed a yeast two-hybrid screen to identify Bcl-2-interacting gene products in an adult mouse brain library. We identified a novel 60-kDa coiled-coil protein, Beclin, which we confirmed interacts with Bcl-2 in mammalian cells, using fluorescence resonance energy transfer microscopy. To examine the role of Beclin in Sindbis virus pathogenesis, we constructed recombinant Sindbis virus chimeras that express full-length human Beclin (SIN/beclin), Beclin lacking the putative Bcl-2-binding domain (SIN/beclinΔBcl-2BD), or Beclin containing a premature stop codon near the 5′ terminus (SIN/beclinstop). The survival of mice infected with SIN/beclin was significantly higher (71%) than the survival of mice infected with SIN/beclinΔBcl-2BD (9%) or SIN/beclinstop (7%) (P < 0.001). The brains of mice infected with SIN/beclin had fewer Sindbis virus RNA-positive cells, fewer apoptotic cells, and lower viral titers than the brains of mice infected with SIN/beclinΔBcl-2BD or SIN/beclinstop. These findings demonstrate that Beclin is a novel Bcl-2-interacting cellular protein that may play a role in antiviral host defense.